Aerodynamic design of a multi-stage industrial axial compressor. (February 2018) - Zhang, Jinhuan; Zhou, Zhenggui; Cao, Hui; Li, Qi
Highlights: This study presents an aerodynamic design method. The method is used for designing multi-stage axial compressors. The design of the first stage is based on the S1/S2 stream surface theory. Subsequent stage designs replicate the first stage design. A five repeated stage axial compressor with a large mass flow rate was designed. Abstract: Axial compressors are widely used in industrial applications; high efficiencies and large operating ranges are main performance requirements for their aerodynamic designs. In this study, an aerodynamic design method for multi-stage axial compressors is proposed. The design of the first stage is based on the S1/S2 stream surface theory, and a repeated stage design method is proposed for subsequent stage designs. And in the first stage design, a multi-point optimization design is used to design the rotor and stator blade profiles for both high efficiencies and large operating ranges. A five repeated stage axial compressor with a large mass flow rate has been designed by this design method. Analysis results of the rotor and stator three-dimensional flow fields indicate that the flow is primarily limited to the S1 stream surface and the two-dimensional design method is applicable; the flow in subsequent stages possesses similar characteristics as the flow in first stage. In addition, the designed five-stage axial compressor has a total pressure ratio that approaches the design goal and a stability margin that exceeds the design goal. The novelty of this study includes two parts, one is the usage of multi-point optimization method for rotor and stator blade design, and the other is the repeated stage design method.